PENGARUH KUALITAS PELAYANAN TERHADAP KEPERCAYAAN NASABAH DAN LOYALITAS NASABAH BANK MANDIRI CABANG VETERAN DENPASAR BALI - Pramana, I Gede Yogi; Rastini, Ni Made (E-Jurnal Manajemen; Vol 5 No 1 (2016), 2016)
This study was conducted to determine the effect of service quality on customer satisfaction and loyalty veteran independent bank branch Denpasar Bali. The research location is on the bank on the road Veteran Denpasar¬-Bali. The site selection was based on several considerations, namely independent bank branch Veteran Denpasar is the central office of the bank in Denpasar, samples taken as many as 150 people with purposive sampling method. Data collected by questionnaires by using a 5-point Likert scale to measure 24 indicators. The analysis technique used is path analysis. These results indicate that the service quality variable positive and significant impact on the trust of customers, service quality variable positive and significant impact on customer loyalty, variable customer confidence positive and significant impact on customer loyalty, and service quality variables affect posiitif on customer loyalty through customer trust Bank Mandiri Branch Veteran, Denpasar-Bali. That is, the better the quality of service the customer confidence is growing, so the trust of customers, the better.
Keywords: Service Quality, Customer Loyalty And Customer Confidence